Impaired endothelial function in the brachial artery after Kawasaki disease and the effects of intravenous administration of vitamin C - Deng, You-Bin; Li, Tian-Liang; Xiang, Hui-Juan; Chang, Qing; Li, Chun-Lei (The Pediatric infectious disease journal, 2003)
Previous studies in patients with a history of Kawasaki disease have focused on vascular endothelial function in coronary arteries, and the endothelial function of systemic arteries is not fully understood. Furthermore the effect of vitamin C on systemic endothelial function after Kawasaki disease has not been elucidated. We attempted to analyze endothelium-dependent vasodilatation in the brachial artery after Kawasaki disease by using high resolution ultrasonography and to investigate whether the acute administration of vitamin C could restore such systemic endothelial dysfunction. We compared 39 patients (7.1 +/- 2.7 years) 1.0 to 9.6 years after acute Kawasaki disease with 17 matched healthy subjects (7.0 +/- 3.1 years) as controls. Using high resolution vascular ultrasound, we measured brachial artery responses to reactive hyperemia (with increased flow causing endothelium-dependent dilatation) and sublingual nitroglycerin (causing endothelium-independent dilatation). The percent change in diameter of the brachial artery induced by reactive hyperemia in the patients with a history of Kawasaki disease (6.2 +/- 3.9%) was significantly lower than that in the control group (14.1 +/- 6.8%; P < 0.0001). No significant difference could be found in percent change in diameter induced by sublingual administration of nitroglycerin between the control (33.2 +/- 13.7%) and the patients with a history of Kawasaki disease (30.6 +/- 9.2%; P = 0.49). There was no significant difference in percent change in diameter of the brachial artery induced by reactive hyperemia between the patients who received gamma-globulin (6.0 +/- 4.0%) and those who did not receive gamma-globulin (7.9 +/- 3.3%; P = 0.33). Intravenous infusion of vitamin C significantly increased the percent change in diameter of brachial artery induced by reactive hyperemia in 19 patients with history of Kawasaki disease (6.6 +/- 3.5 to 13.0 +/- 5.5%; P < 0.0001), whereas no significant increase was seen in the percent change in diameter of brachial artery induced by reactive hyperemia in 20 patients with history of Kawasaki disease after placebo administration (6.5 +/- 4.5 to 7.3 +/- 4.9%; P = 0.20). Our study showed decreased percent change in diameter of the brachial artery induced by reactive hyperemia in patients with history of Kawasaki disease compared with the healthy children, indicating that systemic endothelial dysfunction exits after Kawasaki disease. Although such systemic endothelial dysfunction after Kawasaki disease is not influenced by early treatment with high dose gamma-globulin in the acute stage of Kawasaki disease, it can be restored by the acute intravenous administration of vitamin C.